2014
DOI: 10.1108/ecam-04-2013-0036
|View full text |Cite
|
Sign up to set email alerts
|

Exploring AEC education through collaborative learning

Abstract: Purpose – There is concern that traditional teaching methods (including lectures and tutorials) do not prepare graduates with the generic employability skills required by the construction industry. This has motivated architecture, engineering and construction (AEC) academics to consider the use of student-centred approaches like collaborative learning. However, the effectiveness of collaborative learning approaches has not been widely examined in AEC education. The purpose of this paper is to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
1
12
0
2
Order By: Relevance
“…Dalam Wulandari & Anita (2019) model pembelajaran ini ialah model pembelajaran dimana para siswa/siswi berkolaborasi di suatu kelompok kecil untuk memenuhi tujuan belajar, untuk memecahkan suatu masalah, menyelesaikan suatu latihan, atau memperoleh suatu materi (Armiati & Sastramihardja, 2007). Pembelajaran model kooperatif menekankan kerjasama tim (Chan & Sher, 2014), maka dari itu pembelajaran kooperatif bisa membantu siswa mengkomunikasikan informasi, gagasan, dan sudut pandang yang dimilikinya, serta secara bersama-sama dapat meningkatkan saling pengertian.…”
Section: ) Online-collaborative Learningunclassified
“…Dalam Wulandari & Anita (2019) model pembelajaran ini ialah model pembelajaran dimana para siswa/siswi berkolaborasi di suatu kelompok kecil untuk memenuhi tujuan belajar, untuk memecahkan suatu masalah, menyelesaikan suatu latihan, atau memperoleh suatu materi (Armiati & Sastramihardja, 2007). Pembelajaran model kooperatif menekankan kerjasama tim (Chan & Sher, 2014), maka dari itu pembelajaran kooperatif bisa membantu siswa mengkomunikasikan informasi, gagasan, dan sudut pandang yang dimilikinya, serta secara bersama-sama dapat meningkatkan saling pengertian.…”
Section: ) Online-collaborative Learningunclassified
“…When asymmetric talents create self-sufficiency in a subset of the group, as in one person or a pair being able to solve the whole problem, it detracts from positive interdependence and reduces the motivation for promotive interaction. For positive interdependence, teammates need to see how each partner's role is crucial to the success of the enterprise [66]. If the teams are initially asked to use a variety of skills on a very simple problem, they can develop confidence for more complex scenarios later.…”
Section: Recommendations For Shaping Effective Digitally-enabled Intementioning
confidence: 99%
“…Previous studies and research have shown learning models that can help achieve 21st-century learning goals. Chan & Sher (2014) found that collaborative learning models are tools that can help improve students' general and technical work skills. Meanwhile, the problem-based learning model can encourage students' critical thinking skills (Asyari, Al Muhdhar, Susilo & Ibrohim, 2016).…”
Section: Learning Models Of the 21st Centurymentioning
confidence: 99%
“…The Collaborative Learning (CbL) model is a learning model in which students work in small groups together to achieve learning goals (Gokhale, 1995). This CbL model emphasizes collaborative and collaborative activities (Chan & Sher, 2014). Therefore, this CbL model involves active student participation.…”
Section: Collaborative Learningmentioning
confidence: 99%